TANGGUNG JAWAB NEGARA TERHADAP KERUGIAN WISATAWAN BERKAITAN DENGAN PELANGGARAN HAK BERWISATA SEBAGAI BAGIAN DARI HAK ASASI MANUSIA - Laheri, Putu Eva (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 1 (2015)DO - 10.24843/JMHU.2015.v04.i01.p10, 2015)
This is a research after state responsibility for the damages suffered by tourists in relation with the violation of the right to tourism as a part of Human Rights, aims to describe and analyze about the liability of Indonesian Government to respect, protect and fulfill the right of every individual toward to enjoy his/her rights to tourism under Article 28I (4) of the Indonesian Constitution Year 1945 and Article 8 Statute Number 39 Year 1999 regarding Human Rights. Furthermore this research is willing to assess the circumstances that might create a possibility for tourists to file a claim of compensation against the Indonesian Government for the losses suffered as a result of the failure/the negligence of Indonesian Government to fulfill its responsibilities. Based on statement mentioned above, the question arises, whether in concept, tourists are able to file a claim of compensation against the Indonesian Government in relation with the recognition of the right to tourism as a part of Human Rights? And also in terms of how tourists can possibly file a claim of compensation against the Indonesian Government? The method used in this research is the method of normative legal research using the statute approach, the comparative approach as well as the conceptual approach. Based on the research that has been done, the conclusion is that in concept tourists can file a claim of compensation against the Indonesian Government, if they can prove that the damage or loss is caused by a violation of Human Rights conducted by the Indonesian Government and the result of this research further shows that the claim should be filed together with stating prove that the Indonesian Government has conducted a violation of the rights to tourism as a part of Human Rights.
Keywords: Claim of compensation, Damages suffered, Human Rights, Violation of right to tourism